2012
DOI: 10.1001/jama.2012.339
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Cardiovascular Health Metrics and Associations With All-Cause and CVD Mortality Among US Adults

Abstract: Context Recent recommendations from the American Heart Association aim to improve cardiovascular health by encouraging the general population to meet 7 cardiovascular health metrics: not smoking; being physically active; having normal blood pressure, blood glucose and total cholesterol levels, and weight; and eating a healthy diet. Objective To examine time trends in cardiovascular health metrics and to estimate joint associations and population-attributable fractions of these metrics in relation to all-cause … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

54
640
9
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 708 publications
(712 citation statements)
references
References 54 publications
54
640
9
9
Order By: Relevance
“…We also observed that the prevalence of ideal cardiovascular health among obese people was extremely low over the past 3 decades, remaining consistently <2%, and that very few adult obese participants met the criteria for ideal blood cholesterol health (<5%). These results are consistent with previously reported very low prevalence of meeting cardiovascular health among the general adult population in the United States 33. Consistent with a previous report on the prevalence of CVD risk factors in US adults from 1960 to 2000,16 our results indicated that blood glucose health continued to deteriorate in obese people during the period 1988–2014.…”
Section: Discussionsupporting
confidence: 93%
“…We also observed that the prevalence of ideal cardiovascular health among obese people was extremely low over the past 3 decades, remaining consistently <2%, and that very few adult obese participants met the criteria for ideal blood cholesterol health (<5%). These results are consistent with previously reported very low prevalence of meeting cardiovascular health among the general adult population in the United States 33. Consistent with a previous report on the prevalence of CVD risk factors in US adults from 1960 to 2000,16 our results indicated that blood glucose health continued to deteriorate in obese people during the period 1988–2014.…”
Section: Discussionsupporting
confidence: 93%
“…For dietary patterns in Life's Simple 7, some investigators raised a concern that adherence to the 5 AHA dietary recommendations is challenging 25. In fact, in our study as well as previous ones, the prevalence of ideal diet patterns is low (<1%–6%) 17, 18, 26, 27, 28. This might partially explain no significant association, even with incident MI, an analysis with much higher statistical power than the analysis after incident MI.…”
Section: Discussioncontrasting
confidence: 50%
“…Attainment of these ideal health metrics has been associated with lower incidence of cardiovascular disease, including coronary heart disease, myocardial infarction, heart failure,10, 11, 12, 13, 14 stroke,15 and retinopathy,16 in addition to noncardiovascular conditions, such as cancer 11, 17. Greater attainment of ideal cardiovascular health through midlife to late life is associated with both a lower prevalence of cardiovascular disease in late life and better cardiac structure and function in late life among people free of prevalent cardiovascular disease 18.…”
Section: Introductionmentioning
confidence: 99%